PICA WITH AN UNUSUAL FORM OF PRESENTATION: A CASE REPORT - Acharya, Aditi; Desousa, Avinash; Sonavane, Sushma; Karia, Sagar (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Geophagia is a condition involving the consumption of mud and is a form of eating disorder known as pica. Pica is an unusual craving for ingestion of either edible or inedible substances. Although, pica is not linked to solvent abuse, here we report a middle aged lady with mud eating that responded to selective serotonin-reuptake inhibitors and cognitive behavior therapy. Keywords: Pica, Geophagia, Mud eating.